Standardizing Use of Mepiquat Chloride for Higher Productivity of Densely Planted Bt Cotton Variety - Kaur, Sirat; Singh, Manpreet; Singh, Kulvir (Journal of Farming, 2025)
Standardizing use of mepiquat chloride for higher productivity of densely planted Bt cotton variety” was carried out at the Regional Research Station, Abohar and Regional Research Station, Faridkot during the kharif season of 2021 on Btcotton variety PAU Bt3. The soil of experimental field was silty loam at Abohar and sandy loam at Faridkot. The experiment was laid out in a split plot design with four plant spacings (67.5×15 cm, 67.5×30 cm, 67.5×45 cm and 67.5×60 cm) as main plots and five Mepiquat chloride levels (MC (5%) @ 375 ml ha-1 at squaring, MC (5%) @ 375 ml ha-1 at flowering, MC (5%) @ 750 ml ha-1 at squaring, MC (5%) @ 750 ml ha-1 at flowering and after 15 days and Control (No MC)) as sub plots with three replications. Lowest plant density (67.5×60 cm) and MC (5%) @ 750 ml ha-1 at squaring resulted in significant reduction of plant height, LAI (Leaf Area Index) and dry matter as compared to control at both the locations. Higher boll retention and opened bolls were observed in 67.5×60 cm and MC (5%) @ 750 ml ha-1at flowering. There was no significant effect of both the treatments factors on node count, monopods and sympods. Highest seed cotton yield was obtained with 67.5 ×30 cm (at Abohar) and 67.5×15 cm (at Faridkot) although these two spacing levels were at par with each other. MC (5%) @ 750 ml ha-1 at flowering resulted in 22.9% and 21.3% increase in seed cotton yield over control at Abohar and Faridkot, respectively. Different plant spacings and mepiquat chloride applications showed a non-significant effect on different fibre quality parameters except halo length at Faridkot. At both the locations, highest B:C ratio was observed in 67.5×30 cm and MC @ 750 ml ha-1 at flowering.
Keywords: Bt cotton; plant spacing; plant density; mepiquat chloride; seed cotton yield